Coping with Technological Changes:Regional and National Preparedness in Face of Technical Change - Jari Kaivo-oja; Mikkel Stein Knudsen; Theresa Lauraeus (Palgrave Macmillan, 2022)
The ability to cope with technical change is not evenly distributed geographically. It is possible to evaluate and forecast this ability by creating metrics that capture preparedness to face technical change by looking at multiple factors. This chapter presents selected metrics to measure preparedness and discusses how such metrics can be used with other sources of information about the future changes to create a relevant basis for foresight work that helps societies to adopt and to prepare for the age of digitalization and new forms of manufacturing.
Technical, Economic and Societal Effects of Manufacturing 4.0: Automation, Adaption and Manufacturing in Finland and Beyond